Temporal evolution of single-cell transcriptomes of Drosophila olfactory projection neurons. - Xie, Q.; Brbic, M.; Horns, F.; Kolluru, S.S.; Jones, R.C.; Li, J.; Reddy, A.R.; Xie, A.; Kohani, S.; Li, Z.; McLaughlin, C.N.; Li, T.; et al. (eLife, 2021)
Neurons undergo substantial morphological and functional changes during development to form precise synaptic connections and acquire specific physiological properties. What are the underlying transcriptomic bases? Here, we obtained the single-cell transcriptomes of Drosophila olfactory projection neurons (PNs) at four developmental stages. We decoded the identity of 21 transcriptomic clusters corresponding to 20 PN types and developed methods to match transcriptomic clusters representing the same PN type across development. We discovered that PN transcriptomes reflect unique biological processes unfolding at each stage-neurite growth and pruning during metamorphosis at an early pupal stage; peaked transcriptomic diversity during olfactory circuit assembly at mid-pupal stages; and neuronal signaling in adults. At early developmental stages, PN types with adjacent birth order share similar transcriptomes. Together, our work reveals principles of cellular diversity during brain development and provides a resource for future studies of neural development in PNs and other neuronal types.